Simplifying Child Identity Card Services through the ADA DIA Program: Mempermudah Layanan Kartu Identitas Anak melalui Program ADA DIA - Pitono, Eppy Dian; Rodiyah , Isnaini (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Public service innovation is essential to meet the growing and complex needs of society, particularly in administrative population management. Specific Background: The Child Identity Card (KIA) program serves as a national effort to ensure children's civil rights and legal identity. However, the manual and centralized KIA service in Sidoarjo created access limitations for rural communities. Knowledge Gap: Limited studies have examined local government innovations that bring population services closer to citizens, especially children. Aims: This study aims to describe and analyze the ADA DIA (Ambil Data Anak Dapat KIA) program as an innovation in KIA service delivery at the Krembung District. Results: The findings show that ADA DIA demonstrates relative advantage, suitability with community needs, low complexity, high trialability, and strong observability. Novelty: ADA DIA presents a direct service approach where officers visit schools to collect data, reducing bureaucracy and costs. Implications: The program serves as a replicable model for other districts to improve accessibility and equity in population services for children. Highlights: ADA DIA simplifies KIA service through school-based data collection. Demonstrates low complexity and high community acceptance. Provides a model for inclusive administrative service innovation. Keywords: Innovation, Public Service, Child Identity Card, ADA DIA Program, Krembung District